Isolation and identification of staphylococcus species obtained from healthy companion animals and humans - Thomson, Pamela; García, Patricia; Miles, Jorge; Isla, David; Yáñez, Camilo; Santibáñez, Rodrigo; Núñez, Andrea; Flores Yáñez, Carla.; Río, Camila del; Cuadra, Françoise (MDPI, 2022)
The close contact between people and their pets has generated the exchange of skin microbiota, accompanied by bacteria that present resistance to antibiotics. Staphylococcus spp., opportunistic pathogens present in the skin and mucosa of mammals, have had their importance recognized in human and veterinary medicine. The objectives of this study were to identify Staphylococcus spp. present in isolates from the nostrils of healthy humans, dogs and cats as well as to determine their phenotype of resistance to methicillin. Strain identification was performed by MALDI-TOF mass spectrometry and antimicrobial susceptibility was determined using a disk diffusion assay for 12 antibiotics. Sixty humans (veterinary and technicians), sixty dogs and sixty cats were sampled; of them, 61.6%, 56.6% and 46.6%, respectively, carried Staphylococcus spp. in their nostrils, and only two people carried two different species of Staphylococcus in the only anatomical site sampled. A methicillin-resistant phenotype was present in 48.7% of the humans, 26.5% of the dogs and 57.1% of the cats, and sampled. These results demonstrate the presence of Staphylococcus spp. strains resistant to methicillin in personnel who work in contact with animals, as well as in dogs and cats that entered the same hospital or veterinary clinic, which alerts us to the potential transfer of these strains to or between people, dogs and/or cats.
Keywords: Antimicrobial susceptibility testing; Human; Staphylococcus spp; Resistance; Dogs; Cats